Power Politics, Banking Union and EMU Adjusting Europe to Germany - Donnelly, Shawn (Routledge/UACES Contemporary European Studies, 2018)
This book examines the politics of Banking Union and EMU reform in the EU, and draws lessons for what it means for international politics, both in Europe, and for international relations more broadly. It demonstrates that most of the reforms in Europe to break free of the Eurozone and banking crises in which Europe continues to find itself focus on building up the capacities of national authorities rather than European ones. The result is that national authorities remain largely in control of the decisions and funds that are to be deployed to prevent economic disaster if a single EU bank fails. The likely outcome is an accelerated balkanization of the European market for the foreseeable future. The book also contends that power politics, and realism in particular, is a defining feature of European politics with coercion and enforced national responsibility at the demand of Germany; the dominant form of institution-building that established the responsible sovereignty model, and shut down the possibility of alternatives. In making this case, the book demonstrates that the dominant view in international relations, that power politics best explains the behaviour of states, also apply to the EU. This text will be of key interest to scholars and students of the Eurozone crisis, EU politics, economic policy, and more broadly to political economy, public policy and international relations.